2021
DOI: 10.1080/09540105.2021.1978941
|View full text |Cite
|
Sign up to set email alerts
|

A new high-quality elderberry plant extract exerts antiviral and immunomodulatory effects in vitro and ex vivo

Abstract: Infections of the respiratory system, including common cold and influenza, are affecting people worldwide and are more or less prone to spread depending on the season and viral load of the host. For reducing symptoms and duration of illness, treatment options to standard prescribed drugs are in demand. Natural products could provide immune-supporting treatment alternatives. Elderberry extracts have been used in traditional medicine for the treatment of respiratory infections for decades and numerous studies de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 36 publications
1
9
0
1
Order By: Relevance
“…However, the ethanol-derived EE25 fraction had no potential to modulate and increase the investigated immune responses. This observation is in line with a recent report investigating the effect of an ethanolic extract on cytokine production [ 21 ]. Interestingly, the authors actually observed a reduced expression of TNF-α and IFN-γ, which fits with our results, as we did not see a significant increase in TNF-α and IFN-γ production when cells were incubated with the ethanol extract EE25 compared to the water extract EC15, and derived fractions CPS, BOUND and UNBOUND.…”
Section: Discussionsupporting
confidence: 93%
“…However, the ethanol-derived EE25 fraction had no potential to modulate and increase the investigated immune responses. This observation is in line with a recent report investigating the effect of an ethanolic extract on cytokine production [ 21 ]. Interestingly, the authors actually observed a reduced expression of TNF-α and IFN-γ, which fits with our results, as we did not see a significant increase in TNF-α and IFN-γ production when cells were incubated with the ethanol extract EE25 compared to the water extract EC15, and derived fractions CPS, BOUND and UNBOUND.…”
Section: Discussionsupporting
confidence: 93%
“…Several plants demonstrate a T H 1 to T H 2 shift. For instance, treatment with Nigella sativa favours a shift to a T H 2 cytokine profile in mouse lymphocytes [ 202 ], and in human lymphocytes with Sambucus nigra [ 203 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the aggregate, black elder contains many valuable compounds for general health and may be beneficial to control COVID-19. Recently, Schön et al 167 demonstrated that elderberry extract has antiviral activity and inhibits the release of pro-inflammatory cytokines TNF- and α, IFN-γ, and IL-2, indicating that elderberries act as immunomodulators. Additionally, the elderberry extract possesses substantial antiviral bioavailability, as demonstrated by its high virucidal efficacy against the modified vaccinia virus Ankara, which is reduced by up to 95%.…”
Section: Functional Food Ingredients Were Effective In Virus Infectionsmentioning
confidence: 99%